Vibration control for various structures with time-varying properties via model-free adaptive controller based on virtual controlled object and SPSA. (1st May 2022) - Yonezawa, Ansei; Yonezawa, Heisei; Kajiwara, Itsuro
Graphical abstract: Highlights: A model-free vibration control strategy is considered. An online self-tuning scheme is combined with the model-free controller. The proposed controller is free from controlled object models. The performance of the proposed method is demonstrated by simulations. Abstract: This study presents a simple active vibration controller with a self-tuning mechanism free from a mathematical model of an actual controlled object. First, a virtual controlled object (VCO), which is defined as a single-degree-of-freedom (SDOF) system, is inserted between an actuator model and an actual controlled object. Traditional model-based control theories are applied to a two-degree-of-freedom (2DOF) system composed of the actuator and the VCO instead of a model of the actual controlled object to realize a model-free vibration controller. Then a self-tuning method based on the simultaneous perturbation stochastic approximation (SPSA) is introduced to the VCO-based model-free controller to obtain sufficient damping performances for various controlled objects. The model-free controller design is easily achieved because the traditional model-based control theory can be applied to the 2DOF system composed of the actuator and the VCO. Moreover, the proposed self-tuning mechanism provides sufficient vibration suppression effects for various controlled objects without manual controller tunings. Simulation studies compare the damping performance of the VCO-based model-free adaptive control scheme with that of the conventional approach. The simulations employ five controlled objects with different structures and characteristics, including time-varying properties. The proposed control scheme provides better damping effects than the conventional method for all controlled objects.